Implementation of the Occupational Safety and Health Management System (SMK3) Policy at PT. PLN (Persero) ULP Panam - Nurasyikin, Nurasyikin; Meilani, Nur Laila; Adianto, Adianto (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Occupational safety and health is one aspect of protection and basic rights of every employment. Occupational safety and health are very important for companies and their workforce, this is because their work carries a very high risk, so it is necessary to implement an occupational safety and health management system, in order to minimize the occurrence of work accidents in the workplace or while carrying out work. Work activities carried out by workers at PT. PLN (Persero) ULP Panam is also not immune from the very high risk of work accidents. So, to minimize work accidents, Government Regulation No. 50 of 2012 concerning the Implementation of the Occupational Safety and Health Management System (SMK3) was created with an effort to prevent and reduce work accidents while working. This research uses phenomenology and qualitative research techniques. George Edward III's Theory of Public Policy Implementation as an indicator in the discussion of this research. The location of the research was at PT. PLN (Persero) ULP Panam. Research data was obtained through observation, interviews and document analysis. The results of the research conducted by the author show that in implementing the Policy for Implementing the Occupational Safety and Health Management System at PT. PLN (Persero) ULP Panam, in its implementation, PLN Panam itself still lacks human resources and the inhibiting factor in carrying out work safely is the condition of equipment that does not support occupational safety and health in the field.